A 100 kW cavity-receiver reactor with an integrated two-step thermochemical cycle: Thermal performance under solar transients. (June 2020) - Vidal, Alfonso; Gonzalez, Aurelio; Denk, Thorsten
Abstract: A future sustainable economy based on hydrogen will require large-scale hydrogen production processes in a CO2 emission-free way. Within this context, solar-driven thermochemical water splitting cycles have been proposed as a promising alternative for hydrogen mass production with the use of concentrated solar energy as the principal source to provide the process heat. Numerous solar thermochemical water-splitting cycles have been investigated for hydrogen production, each with different sets of operating conditions, engineering challenges, etc. Challenges remain in the demonstration of commercially viable thermochemical cycles and reactors, in particular, efficient and robust reactor designs compatible with solar concentrating systems. A 100 kWth multi-tubular cavity reactor for hydrogen production integrated in a solar tower has been used as test bed to demonstrate the technological feasibility of a thermochemical process with incident solar transients. The work presented on this paper dealt with integration of a cavity reactor into a solar concentrating system running a ferrite based solar thermochemical water splitting cycle. This work also explores the thermal performance of a cavity reactor beyond optimal operational conditions governed by transient cloud events. These conditions emerge as a relevant matter to be considered because they have not been studied so far. Highlights: Cavity reactor configuration for solar concentrating applications. Aiming point strategy approach for integration of the cavity reactor in a solar tower. Thermal performance of cavity reactor under solar transients. Analysis of heat losses and thermal efficiency of the cavity reactor.